Faktor Risiko Lingkungan Kejadian Leptospirosis di Jawa Tengah (Studi Kasus di Kota Semarang, Kabupaten Demak dan Pati) - Riyaningsih Riyaningsih; Suharyo Hadisaputro; suhartono suhartono (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background : Leptospirosis is zoonotic disease caused by Leptospira bacteria and transmitted to human through contact with animal urine and contaminated environment.The number of cases increased since 2005, particulary Semarang, Demak, and Pati regency. The purpose of this study is to analyze environmental risk factors related to leptospirosis incidence in Central Java. Method : This research was an explanatory research with  observational method using  case control design. The subjects were 60 cases and 60 controls recruted with  inclusion criteria. Diagnosis  of control was based on  clinical diagnosis and examination of blood sample with  Leptotek Lateral Flow. The data was analyzed in univariate, bivariate and multivariate tests using logistic regression. Result : The results of this research found that  physical environmental factors that influenced the incidence of leptospirosis were stagnant water of the ditch (OR = 3.5; 95% CI: 1,282-9,301; p = 0.014) and habit of taking bath  or washing in the river (OR = 7.5; 95% CI: 1.534- 36.185; p = 0.014). Recomendation: It was sugested for Health Departement to control the risk factors of physical environment by cooperating with relevant agencies, especially PROKASIH (Clean River Program). People need to keep cleaning the house and the neighborhood, especially the existence of  pools of water around the house and do not get a shower and take out the trash / dead mouse in a river. Keywords : Leptospirosis, Environment, Risk Factors